Розвиток методу активної послідовної корекції з використанням нечіткого керування в системах регулювання електроприводами складних електромеханічних установок - Півняк, Г.Г.; Бешта, О.С.; Хілов, В.С. (Видавничий дім "Академперіодика" НАН України, 2007)
Using the method of active successive correction and the ideas of fuzzy control theory, we find the additional contour correcting regulators which suppress the influence of elastic properties of a transmission on the control system dynamics.